2009
DOI: 10.3904/kjim.2009.24.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Chest Computed Tomography (CT) Immediately after CT-Guided Transthoracic Needle Aspiration Biopsy as a Predictor of Overt Pneumothorax

Abstract: Background/AimsThis study examined the correlation between pneumothorax detected by immediate post-transthoracic needle aspiration-biopsy (TTNB) chest computed tomography (CT) and overt pneumothorax detected by chest PA, and investigated factors that might influence the correlation.MethodsAdult patients who had undergone CT-guided TTNB for lung lesions from May 2003 to June 2007 at Seoul National University Bundang Hospital were included. Immediate post-TTNB CT and chest PA follow-up at 4 and 16 hours after CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…In the present study, pneumothorax developed in 30% of CTLB procedures, comparable to previous studies [9,20]. Of all cases of pneumothorax, 16.1% was delayed occurrence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, pneumothorax developed in 30% of CTLB procedures, comparable to previous studies [9,20]. Of all cases of pneumothorax, 16.1% was delayed occurrence.…”
Section: Discussionsupporting
confidence: 91%
“…Of all cases of pneumothorax, 16.1% was delayed occurrence. In other studies involving delayed pneumothorax, the proportion ranged from 7.1% to 29.6% of the overall rate of pneumothorax [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 87%
“…In a comparative study between immediate CT scans and follow-up chest radiography after TFNAB, Noh et al reported that the overall incidence of delayed pneumothorax was 2.6% [13]. In our study, the incidence of delayed pneumothorax was 1.1% (1/94 procedures).…”
Section: Discussionmentioning
confidence: 49%
“…This radiographically defined pneumothorax risk tends to be much higher than if pneumothorax were based on clinical criteria, or even chest x-ray. For example, Noh et al 18 contrasted the rate of pneumothorax observed by CT immediately post-biopsy (25%) with the much lower rate of pneumothorax identified by chest x-ray or clinical symptoms 4–16 hours after biopsy (12%). This “clinical” pneumothorax rate of 12% closely approximates the 15% risk of pneumothorax estimated by Wiener et al 4 Similarly, the median risk of pneumothorax requiring chest tube estimated based on the single-institution case series (4%) is similar to the 6% risk of pneumothorax requiring chest tube identified by Wiener et al in their multi-institution analysis.…”
Section: Resultsmentioning
confidence: 99%